From Planning to Agility: What Allows SMEs to Pivot Successfully in Highly Volatile Business Environments? : A Bibliometric and Systematic Literature Review (B-SLR) - Lehtoranta, Frans-Emil (My University, 2026)
Strategic management literature has traditionally relied on linear planning frameworks that assume a predictable future. However, in the contemporary business landscape characterized by volatility, uncertainty, complexity, and ambiguity (VUCA), these static models frequently fail. Small and Medium-sized Enterprises (SMEs) are particularly vulnerable to these environmental shocks due to the ”liability of smallness” and a lack of financial slack resources. Against this background, this study investigates the strategic transition from static planning to adaptive execution. The objective is to identify the specific operational mechanisms and dynamic capabilities that enable resource-constrained firms to execute successful strategic pivots during periods of crisis. The research employs a rigorous mixed-method Bibliometric-Systematic Literature Review (B-SLR) protocol to ensure both structural breadth and contextual depth. Data collection was conducted via the Scopus and Web of Science databases following the PRISMA guidelines. First, a quantitative Bibliometric Analysis was performed on a dataset of 1202 documents to visualize the intellectual structure and evolutionary trajectory of the field. Second, a qualitative Systematic Literature Review (SLR) was conducted on a finalized sample of 78 articles. This sample was constructed using a purposive strategy that combined high-impact foundational articles with highly relevant recent studies (2023–2025) to mitigate citation time-lag bias. These articles were analysed using a concept-centric matrix and thematic synthesis to isolate the specific enablers of adaptation. The bibliometric findings identify a bimodal evolution in the field, revealing a paradigmatic shift from strategy implementation toward resilience and entrepreneurial agility following the onset of global crises in 2019. The qualitative synthesis constructs a ”Strategic Agility Architecture” (SAA), demonstrating that SMEs overcome resource constraints by orchestrating three dynamic meta-capabilities: strategic sensitivity, leadership unity, and resource fluidity. The results indicate that successful pivoting is enabled by specific antecedents: digital capabilities serve as ”options generators” for sensing market shifts; psychological capital and leadership unity facilitate rapid decision-making; and iterative process enablers, such as Lean Startup methodologies, replace rigid forecasting with experimentation. Furthermore, the evidence highlights that SMEs utilize entrepreneurial bricolage and network capabilities to substitute for the lack of internal buffers. The thesis concludes that in volatile environments, resilience is best conceptualized as ”creative reconstruction,” where firms utilize continuous strategic renewal to achieve sustainable competitive advantage.

Strategisen johtamisen kirjallisuus on perinteisesti nojannut lineaarisiin suunnittelumalleihin, jotka olettavat tulevaisuuden olevan ennustettavissa. Nykypäivän liiketoimintaympäristöä luonnehtivat kuitenkin epävakaus, epävarmuus, monimutkaisuus ja tulkinnanvaraisuus (VUCA), minkä seurauksena nämä staattiset mallit osoittautuvat usein riittämättömiksi. Pienet ja keskisuuret yritykset (pk-yritykset) ovat erityisen haavoittuvia ympäristön shokeille johtuen ”pienuuden rasitteesta” (liability of smallness) ja puskuriresurssien puutteesta. Tätä taustaa vasten tutkimus tarkastelee strategista siirtymää staattisesta suunnittelusta mukautuvaan toimeenpanoon. Tutkimuksen tavoitteena on tunnistaa ne toiminnalliset mekanismit ja dynaamiset kyvykkyydet, jotka mahdollistavat resurssiniukkojen yritysten onnistuneet strategiset suunnanmuutokset (pivoting) kriisitilanteissa. Tutkimuksessa hyödynnetään monimenetelmällistä kirjallisuuskatsausta (B-SLR), joka varmistaa sekä laajan yleiskuvan että syvällisen kontekstuaalisen ymmärryksen. Aineisto kerättiin Scopus- ja Web of Science -tietokannoista noudattaen PRISMA-ohjeistusta. Ensimmäisessä vaiheessa suoritettiin kvantitatiivinen bibliometrinen analyysi 1202 dokumentista alan intellektuaalisen rakenteen ja kehityskaaren kartoittamiseksi. Toisessa vaiheessa toteutettiin laadullinen systemaattinen kirjallisuuskatsaus (SLR) 78:sta artikkelista. Lopullinen otos muodostettiin yhdistämällä alan vaikuttavimmat viitatut artikkelit sekä tuoreet, ajankohtaiset tutkimukset (2023–2025). Aineisto analysoitiin hyödyntäen käsitekeskeistä matriisia ja teema-analyysiä adaptaation mahdollistajien eristämiseksi. Bibliometriset tulokset osoittavat kirjallisuudessa tapahtuneen selkeän paradigman muutoksen perinteisestä strategian toimeenpanosta kohti resilienssiä ja yrittäjämäistä ketteryyttä vuoden 2019 jälkeen. Teema-analyysi tunnistaa ”strategisen ketteryyden arkkitehtuurin” (Strategic Agility Architecture), jossa pk-yritykset voittavat resurssirajoitteet organisoimalla kolmea dynaamista kyvykkyyttä: strategista herkkyyttä, johdon yhtenäisyyttä ja resurssien joustavuutta. Tulokset osoittavat, että onnistunut suunnanmuutos perustuu tiettyihin mahdollistajiin: digitaaliset kyvykkyydet luovat vaihtoehtoja markkinamuutosten havainnointiin, psykologinen pääoma ja johdon yhtenäisyys nopeuttavat päätöksentekoa, ja iteratiiviset prosessit kuten Lean Startup -menetelmät korvaavat jäykät ennusteet kokeilukulttuurilla. Lisäksi tutkimus korostaa, että pk-yritykset hyödyntävät verkostoja ja ”bricolage”-toimintamallia korvatakseen puskuriresurssien puutteen. Tutkielman johtopäätöksenä on, että epävakaissa ympäristöissä resilienssi on ymmärrettävä ”luovana jälleenrakennuksena”, jossa yritykset uudistavat jatkuvasti liiketoimintamallejaan saavuttaakseen kestävän kilpailuedun.
Keywords: small and medium-sized enterprises; agility; dynamic capabilities; volatility (societal properties); resilience; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development